2008
DOI: 10.1098/rspb.2008.0589
|View full text |Cite
|
Sign up to set email alerts
|

The look of royalty: visual and odour signals of reproductive status in a paper wasp

Abstract: Reproductive conflicts within animal societies occur when all females can potentially reproduce. In social insects, these conflicts are regulated largely by behaviour and chemical signalling. There is evidence that presence of signals, which provide direct information about the quality of the reproductive females would increase the fitness of all parties. In this study, we present an association between visual and chemical signals in the paper wasp Polistes satan. Our results showed that in nest-founding phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 43 publications
1
30
0
1
Order By: Relevance
“…Reproductive status (measured as ovarian development) was found to be linked to variation of visual signals both in the stenogastrine wasp L. vechti (Baracchi et al 2013) and in P. satan (Tannure-Nascimento et al 2008), being the wasps with more developed ovaries (i.e. dominant individuals) those with more dark facial markings.…”
Section: Status Recognition and Quality Signalsmentioning
confidence: 98%
“…Reproductive status (measured as ovarian development) was found to be linked to variation of visual signals both in the stenogastrine wasp L. vechti (Baracchi et al 2013) and in P. satan (Tannure-Nascimento et al 2008), being the wasps with more developed ovaries (i.e. dominant individuals) those with more dark facial markings.…”
Section: Status Recognition and Quality Signalsmentioning
confidence: 98%
“…Examples include the chirps of giant pandas [1], the visual signals of some social insect species [2] and the sexual swellings of baboons [3]. Group-living social animals, such as many primates, receive such signals from group members with whom they have a history of previous interactions.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the degree of ovarian development is closely relatedto both body size and the function performed by the foundress. Other studies have shown that foundresses performing reproductive functions (i.e., alpha and solitary), must invest more in ovarian development (Turillazzi & Pardi, 1977;Dropkin & Gamboa, 1981;Fukuda et al, 2003;Tannure-Nascimento et al, 2008). Moreover, auxiliary foundresses performing activities with high energy costs, such as foraging for resources, are likely to undergo ovarian regression (Keeping, 2000;Cervo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that in pleometrotic foundations of IF polistine wasps, the colony reproductive function is aggressively disputed among potential females, and larger females have increased chances of subduing smaller competitors (Cant & Field, 2001;Tannure-Nascimento et al, 2008). Under these conditions, the reproductive organization is highly dependent on a dominance hierarchy, with larger females occupying higher positions in this hierarchy (Turillazzi & Pardi, 1977;Cervo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation